PERAN MEDIA SOSIAL DALAM MEMPENGARUHI PEMAHAMAN HUKUM KELUARGA ISLAM DI KALANGAN GENERASI MUDA: STUDI FENOMENOLOGI - Apriansyah, Apriansyah (Jurnal GeoCivic, 2024)
In the context of Islamic family law, social media allows younger generations to explore different views and interpretations of the legal principles. However, not all information available on social media is educational or accurate. Many users may not have a formal educational background in law or a deep understanding of Islamic principles.This research examines the phenomenon of transforming the understanding of Islamic family law among the younger generation through social media with a qualitative-phenomenological approach. The research focuses on the experiences and meanings of the younger generation in accessing, understanding, and implementing Islamic family law through digital platforms. Data collection was conducted through in-depth interviews with 20 informants, virtual observation on social media platforms, and digital document analysis.The results show a significant shift in the way young people interpret and access knowledge of Islamic family law, which is marked by the democratization of access to information, the transformation of religious authority, and the formation of virtual learning communities. This research produces theoretical propositions about the dynamics of learning Islamic family law in the digital era.